ANALISIS PENGEMBANGAN CAGAR BUDAYA WARUGA SEBAGAI POTENSI PARIWISATA DI DESA SAWANGAN KABUPATEN MINAHASA UTARA - Walansendow, Agustinus; Alexander, Nelson; Ruslani, Ruslani; Pangkey, Stevie (PolimdoSains, 2025)
Waruga Cultural Reserve is one of the tourist attractions that attracts attention in North Minahasa Regency. This thesis aims to analyze the tourism potential of the Waruga Cultural Heritage and to determine the potential using SWOT. Next, a SWOT analysis is carried out to see the potential that exists in the Waruga Cultural Heritage, where the potential that exists in the Waruga Cultural Heritage is still very large, therefore management is carried out. The data collected is processed by reduction, then the data is described in narrative form and then the data is concluded. to get research results. It is hoped that the results of this research will provide a comprehensive picture of the tourism potential of the Waruga Cultural Heritage and provide recommendations regarding sustainable tourism development. It is also hoped that this research can become a reference for related parties in making policies regarding the management and marketing of the Waruga Cultural Heritage tourist attraction in North Minahasa Regency